Indiscriminate behavior observed in the strange situation among institutionalized toddlers: relations to caregiver report and to early family risk - Oliveira, P. S.; Soares, I.; Martins, C.; Silva, J. R.; Marques, S.; Baptista, J.; Lyons-Ruth, K. (Infant Mental Health Journal, 2012)
Socially disinhibited or indiscriminate behavior (IB) has traditionally been investigated using caregiver reports. More recently, an observational measure based on the Strange Situation Procedure (M. Ainsworth, M. Blehar, E. Waters, & S. Wall, 1978), the Rating of Infant and Stranger Engagement (RISE; C. Riley, A. Atlas-Corbett, & K. Lyons-Ruth, 2005), was validated in home-reared at-risk children. The present study aimed to validate the RISE in an institutionally reared sample using the caregiver report, to assess whether IB assessed with the RISE was elevated among the institutionalized children, and to explore potential risk factors associated with IB. The study was conducted among 74 institutionalized toddlers aged 11 to 30 months. Sociodemographic questionnaires were used to assess pre-admission experiences, and aspects of institutional placement were coded from the children’s files in the institution and staff’s report. Institutionalized children displayed high frequencies of IB as assessed on the RISE, and this instrument was validated against caregiver report. Pre-admission experiences of the institutionalized children in their biological families—namely, prenatal risk and maternal emotional neglect risk—predicted IB. Results suggest that the RISE is adequate to use among institutionally reared toddlers and point to aspects of the early familial environment that may be implicated in IB.